2016
DOI: 10.1007/s10552-016-0799-1
|View full text |Cite
|
Sign up to set email alerts
|

A family-based study of gene variants and maternal folate and choline in neuroblastoma: a report from the Children’s Oncology Group

Abstract: Purpose Neuroblastoma is a childhood cancer of the sympathetic nervous system with embryonic origins. Previous epidemiologic studies suggest maternal vitamin supplementation during pregnancy reduces the risk of neuroblastoma. We hypothesized offspring and maternal genetic variants in folate-related and choline-related genes are associated with neuroblastoma and modify the effects of maternal intake of folate, choline and folic acid. Methods The Neuroblastoma Epidemiology in North America (NENA) study recruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…In fact, several investigators have successfully leveraged CCRN for etiologic studies of several childhood cancers. [6][7][8][9][10][11][12] Despite these accomplishments, however, questions remain about the overall representativeness of the resource.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, several investigators have successfully leveraged CCRN for etiologic studies of several childhood cancers. [6][7][8][9][10][11][12] Despite these accomplishments, however, questions remain about the overall representativeness of the resource.…”
Section: Introductionmentioning
confidence: 99%
“…Between 2008 and 2017, more than 50,000 children treated at COG member institutions were enrolled on CCRN, providing a rich resource for epidemiologic investigations. In fact, several investigators have successfully leveraged CCRN for etiologic studies of several childhood cancers 6‐12 . Despite these accomplishments, however, questions remain about the overall representativeness of the resource.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, to determine whether these 16p11.2 microdeletions arose de novo or were inherited, we considered four cases for which parental DNA had been collected through the Neuroblastoma Epidemiology in North America (NENA) study 52 and WGS had been performed through the GMKF Pediatric Research Program (Figure 3 and Table S7). By comparing relative coverage and low-frequency variants within the deleted region in the children to the same data from their parents, we concluded that the deletion arose de novo in three of four children; of these, two deletions arose on the maternal allele and one on the paternal allele.…”
mentioning
confidence: 99%
“…Then, by determining a threshold for q -values to declare significant findings in multiple comparisons, we can control the expected proportion that declared associations are truly null. In this study, we used a threshold of 0.2, which was also adopted by recent studies 35 , 36 . Using such a less stringent threshold should enable us to find moderate associations, while controlling a reasonable FDR.…”
Section: Discussionmentioning
confidence: 99%